2021
DOI: 10.1101/2021.08.05.455128
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A TIR-1/SARM1 phase transition underlies p38 immune pathway activation in theC. elegansintestine

Abstract: Intracellular signaling regulators can be concentrated into membrane-free, higher-ordered protein assemblies to initiate protective responses during stress — a process known as phase transition. Here, we show that a phase transition of the C. elegans Toll/interleukin-1 receptor domain protein (TIR-1), a homolog of the mammalian sterile alpha and TIR motif-containing 1 (SARM1), primes host immune defenses when dietary sterols are limited to handle subsequent bacterial infection. TIR-1/SARM1 is an upstream compo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 97 publications
(205 reference statements)
0
12
0
Order By: Relevance
“…Previously, we used clustered regularly interspaced short palindromic repeats (CRISPR)-Cas9 to engineer a C. elegans strain that expresses TIR-1/SARM1 protein tagged with the fluorophore wrmScarlet at its endogenous genomic locus. 12 We observed that pathogen infection induces TIR-1::wrmScarlet multimerization into large protein assemblies, or puncta, in the intestinal epithelium. 12 Here, we sought to characterize the mechanism by which infection promoted TIR-1/SARM1 assembly to activate the p38 PMK-1 innate immune pathway.…”
Section: Tir-1/sarm1 Is Expressed On Lysosome-related Organelles In C...mentioning
confidence: 88%
See 4 more Smart Citations
“…Previously, we used clustered regularly interspaced short palindromic repeats (CRISPR)-Cas9 to engineer a C. elegans strain that expresses TIR-1/SARM1 protein tagged with the fluorophore wrmScarlet at its endogenous genomic locus. 12 We observed that pathogen infection induces TIR-1::wrmScarlet multimerization into large protein assemblies, or puncta, in the intestinal epithelium. 12 Here, we sought to characterize the mechanism by which infection promoted TIR-1/SARM1 assembly to activate the p38 PMK-1 innate immune pathway.…”
Section: Tir-1/sarm1 Is Expressed On Lysosome-related Organelles In C...mentioning
confidence: 88%
“…12 We observed that pathogen infection induces TIR-1::wrmScarlet multimerization into large protein assemblies, or puncta, in the intestinal epithelium. 12 Here, we sought to characterize the mechanism by which infection promoted TIR-1/SARM1 assembly to activate the p38 PMK-1 innate immune pathway.…”
Section: Tir-1/sarm1 Is Expressed On Lysosome-related Organelles In C...mentioning
confidence: 88%
See 3 more Smart Citations